2016
DOI: 10.1183/13993003.01444-2015
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting US ivacaftor outcomes and cost in cystic fibrosis patients with the G551D mutation

Abstract: Ivacaftor, a breakthrough treatment for cystic fibrosis (CF) patients with the G551D genetic mutation, lacks long-term clinical and cost projections. This study forecasted outcomes and cost by comparing ivacaftor plus usual care versus usual care alone.A lifetime Markov model was conducted from a US payer perspective. The model consisted of five health states: 1) forced expiratory volume in 1 s (FEV1) % pred ≥70%, 2) 40%≤ FEV1 % pred <70%, 3) FEV1 % pred <40%, 4) lung transplantation and 5) death. All inputs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…98,99 The drug is also exceptionally expensive, costing upwards of $300,000 per year. 100 Nevertheless, the clinical benefits afforded to this subset of CF patients are enormous and it is likely they will experience a lower rate of lung transplantation compared to those receiving traditional care as a consequence of less severe pulmonary involvement. 100 A recent case report by Chang et al 101 demonstrated reversal of CF CRS with both subjective and objective findings after treatment with ivacaftor.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…98,99 The drug is also exceptionally expensive, costing upwards of $300,000 per year. 100 Nevertheless, the clinical benefits afforded to this subset of CF patients are enormous and it is likely they will experience a lower rate of lung transplantation compared to those receiving traditional care as a consequence of less severe pulmonary involvement. 100 A recent case report by Chang et al 101 demonstrated reversal of CF CRS with both subjective and objective findings after treatment with ivacaftor.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
“…100 Nevertheless, the clinical benefits afforded to this subset of CF patients are enormous and it is likely they will experience a lower rate of lung transplantation compared to those receiving traditional care as a consequence of less severe pulmonary involvement. 100 A recent case report by Chang et al 101 demonstrated reversal of CF CRS with both subjective and objective findings after treatment with ivacaftor. The patient experienced rapid resolution of sinonasal symptoms within four weeks, but encountered prompt recurrence of sinus disease upon treatment cessation.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
“…11 No studies have reported the contribution of spending on these products to overall expenditures for insured patients with CF, although one modeling study was published in 2016. 12 In this study, we describe current trends in health care expenditures for commercially insured patients with CF in the US.…”
mentioning
confidence: 99%
“…Furthermore, ivacaftor monotherapy did not demonstrate clinical efficacy in CF subjects homozygous for the F508del CFTR variant, indicating it's requirement for appreciable CFTR at the plasma membrane for drug effect . In addition to these acute effects, prolonged treatment of CF patients with the G551D CFTR mutation reduces the loss of lung function over time relative to untreated controls and reduces mortality in patients with advanced disease . Thus, ivacaftor has the capacity to modify the course of CF disease in certain CF populations.…”
Section: Potentiation Of Cftrmentioning
confidence: 99%
“…49 In addition to these acute effects, prolonged treatment of CF patients with the G551D CFTR mutation reduces the loss of lung function over time relative to untreated controls and reduces mortality in patients with advanced disease. 50,51 Thus, ivacaftor has the capacity to modify the course of CF disease in certain CF populations.…”
Section: Potentiation Of Cftrmentioning
confidence: 99%